FAKTOR-FAKTOR YANG BERPENGARUH PADA KEUNGGULAN KOMPETITIF UKM BATIK - Arum Ardianingsih; Amalia Ilmiani; Wenty Ayu Sunardjo (LPPM Universitas Pekalongan, 2017)
SMEs are the crushers of the people's economy and many grow rapidly in the city of Pekalongan especially SMEs batik. In recently, there has been a decrease of batik sales turnover which is faced by small scale batik entrepreneurs (SMEs) in Pekalongan City. Some of the causal factors include batik products they can not compete with batik textile products that flood domestic markets. This study aims to formulate efforts to increase the competitive advantage of SMEs batik through strategy implementation of SAK ETAP for the preparation of financial statements and e- commerce for online marketing of batik products. Data collection was done by direct observation and structured interview (guided interview) and questionnaires distribution to obtain complete primary data, while secondary data was collected by documentation technique from various relevant sources. Data analysis was done by validity test, reliability, classical assumption test, descriptive analysis and multiple linear regression. The results show that SAK ETAP and Online Marketing have a positive influence on competitive advantage of SMEs Batik.